Conceptualizing of Aging Literature: A Global Perspective - Sigdel, Keshab (The Outlook: Journal of English Studies, 2021)
Aging is generally represented by two stereotypes that present distinctly opposite views: the first views it as a stage of celebration relating it to experience and wisdom. The second is associated with a lamentation on the loss of physical and emotional vigor. There are organized bodies of literature about and for a specific group of the population that includes children literature, young-adult literature. But, there is no such organized body of literature that describes the unique life experiences, physical and psychological conditions, needs, and personal and social relationships of aging people. Though these issues have sporadically appeared in different literary texts, there is still a need to theorize aging literature from academic and other disciplinary perspectives. In this context, this paper serves three-fold objectives: first, it surveys various endeavors to understand aging from both eastern and western perspectives; secondly, it attempts to conceptualize literature on aging by referring to few representations of aging in literary texts; finally, it presents the prospect of literature of aging as a new field of creativity and scholarship.